Design of organic fertilizer pellet machine with a capacity of 170.90 Kg/Hour using verein deutcher ingenieure 2222 method - Prasetio Aji Nugroho; Subekti Subekti; Arvian Iswahyudi (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Due to population expansion and heavy consumption, there has been an increase in household garbage in recent years. One of the waste processing techniques that is kind to the environment is turning organic waste into organic fertilizer. Pellets created from organic fertilizer will be more convenient to use and effective. This study aims to construct an organic fertilizer pellet printing machine using the VDI 2222 method to turn organic fertilizer into pellets. this design approach is used to make sure the finished product or system satisfies defined technical requirements and customer needs. A variation of the design for an organic fertilizer pellet machine has been created based on the research, and the design evaluation is based on a survey. The third machine variation was picked as the best machine variant based on the design's outcomes. This machine is made of materials that are generally accessible on the market, has a solid construction, and a simpler manufacturing procedure. The organic fertilizer pellet mill can produce 8 mm x 22 mm pellets at a rate of 170.90 kilograms per hour. An electric motor and coupler acting as a gearbox transmission link power this machine. UNP Steel was used to construct the framework to increase strength and lessen vibration